Developing Papua Within the Framework of Diversity: A National Defence Perspective - Werijon, Werijon; Risman, Helda; Surryanto D.W., (Advances in Social Sciences Research Journal, 2020)
ABSTRACT The approach to developing apua throughout the years of Indonesia's national leadership has brought considerable improvement to the island of Papua. Indonesia’s First President, Soekarno has laid the foundation of Indonesia's geopolitics in the world political order stretching from Sabang in the west to Merauke (Papua) in the east. Sustainable development in Papua continues to date in various sectors, from infrastructure to the socio-cultural development of the Papuan people. A development program focusing on a respect to-diversity (kebhinnekaan) approach establishes Papua as an integral-nationalistic part of Indonesia under the outline of total sovereignty. Paradoxically, there are still small groups that raise the issue of Free Papua as a manifestation of separatism, either the armed movement in Papua or the dissemination of political issues in international forums. This phenomenon then becomes the focus of this paper and launched the main question, on how Indonesia manages to develop Papua within the frame of diversity from the perspective of national defense. The qualitative approach uses in-depth analysis based on the theory of national defense and theory of development to explain the emerging phenomena. Inquiries toward Papua-related negative issues found that they have the spirit and goal to separate Papua from Indonesia. Through this paper, it is revealed that a constructive development with the mentioned approach has gradually succeeded in building up minds and hearts of the Papuan people under nationalistic ties, as well as becoming the main bulwark for national Defence and eliminating separatism activities. Keywords: Development; Diversity; National Defence; Papua; Separatism